Î²-Arrestin2 regulates the rapid component of delayed rectifier K+ currents and cardiac action potential of guinea pig cardiomyocytes after adrenergic stimulation - Shi, Erdan; Zhou, Xiaozhu; Li, Dongcheng; Zhang, Yuzhen; Yuan, Jiamin; Zou, Jiangang (Cellular and Molecular Biology, 2019)
A decrease in the rapid component of delayed rectifier potassium current (IKr) during chronic heart failure (CHF) prolongs action potential (AP), and plays a key role in the pathogenesis of ventricular arrhythmias. Î²-Arrestin2 has been shown to restore the inotropic reserve of Î²-adrenergic regulation, but little or nothing is known about its effect on intrinsic channel. This study investigated the role of Î²-arrestin2 in the regulation of cardiac hERG/IKr potassium channel and AP during chronic adrenergic stimulation. Single left ventricular myocytes were isolated from guinea pig heart, and were transfected with adenovirus encoding Î²-arrestin2, or Î²-arrestin2 siRNA or an empty adenovirus. Cell cultures containing 10 nM isoproterenol, 1 nM phenylephrine or vehicle alone (control medium) were electro-physiologically examined after 48 h of incubation. Action potential duration at 50 and 90 % of repolarization (APD50 and APD90) were measured using whole-cell patch-clamp recording. Sustained adrenergic stimulation significantly reduced the density of the IKr current (p < 0.001). Î²-Arrestin2 expression in cell cultures treated with isoproterenol or phenylephrine was significantly downregulated after adrenergic stimulation (p < 0.001). Overexpression of Î²-arrestin2 significantly attenuated isoproterenol or phenylephrine-induced reduction in IKr current. It also prevented the phenylephrine-induced prolongation of AP (p < 0.05 for APD50 and p < 0.001 for APD90), but did not significantly affect AP profile after exposure of the cardiomyocytes to isoproterenol (p > 0.05). Therefore, Increased levels of Î²-Arrestin2 weaken dysregulation of IKr current and prevent excessive AP prolongation, making it an effective anti-arrhythmic strategy.